The Effectiveness of Gallery Walk and Simulation (GALSIM) to Improve Students’ Achievement in Fiqh Learning - I Ismail; Sri Anitah W; S Sunardi; Dewi Rochsantiningsih (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
This article presents the efforts of teachers in enhancing students’ achievement through the implementation of a cooperative learning model: Gallery Walk and Simulation (GALSIM). This classroom action research aims to describe the improvement of students’ achievement of Fiqh subject matter. The data was collected by observation, actions, documents, and tests. This two-cycle research used four steps i.e. planning, action, observation and reflection in each cycle. The results show that the implementation of GALSIM could improve students’ activity along the learning process. Moreover, the implementation of this model could also improve students’ achievement at the end of their study on Fiqh.